A trianoni békeszerződés hosszú távú gazdasági következményei - Kaposi, Zoltán (Közép-Európai Közlemények, 2010)
This study examines how the long run effects of the Treaty of Trianon have influenced the Hungarian economic development. The immediate consequence of the dissolution of the Habsburg Empire was the loss of the protected market. The Hungarian economy became an open economy, which was strongly influenced by the changes of the world economy. The internal structure of the Hungarian economy transformed. Against every difficulty, a significant production growth had been starting after 1924. The amount of the national debt has begun to increase in the times of the Monarchy, continued this tendency between the World Wars, intensified under the Socialist regime and has been lasting till nowadays. The government debt reached its maximum nowadays; the GDP related gross debt is about 80%. The adaptability of the Hungarian economy has been poor since 1920. An important consequence is the growth of the bureaucracy. As a result, every fourth person is employed by the state in 2010.